Analisa Pencahayaan Alami Ruang Kelas pada Sekolah SMA N-1 Tanjung Pura Menggunakan Dialux Evo 11.1 - Khoirunnisa, Arju; Safyan, Adi; Fidyati, Fidyati (Jurnal Etnik: Ekonomi-Teknik, 2023)
Natural lighting (Daylighting) is the use of natural light as the main source of sunlight for lighting. In an educational environment, the classroom is the space that is most frequently used compared to other spaces. Therefore, adequate lighting is needed to support teaching and learning activities inside. Based on observations at SMA N-1 Tanjung Pura, classrooms tend to have low lighting levels, which are influenced by factors such as vegetation, surrounding buildings and limited land. This research aims to analyze the effectiveness of natural lighting, especially the natural lighting factor (daylight factor), in the classrooms of SMA N-1 Tanjung Pura in accordance with the SNI standard SNI 03-6197-2020, which sets a lighting level of 350 Lux. The research method uses computer simulation with Dialux Evo 11.1 software. The research results show that some classrooms do not meet the standards because they have lighting levels that are lower or higher than those specified in the standards.